2017
DOI: 10.1002/adsc.201700577
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Acyloxycyanation of Alkynes with Acetonitrile: Regioselective Construction of Cyclic Acrylonitriles by 6‐endo or 5‐exo Cyclization

Abstract: An efficient difunctionalization of alkynes by tandem iodolactonization and coppercatalyzed cyanation using acetonitrile as a cyanating reagent is reported for the first time. This approach can afford cyano-containing isocoumarin or phthalide derivatives in good yields by careful choice of the carboxylate nucleophiles and electrophilic iodine sources. Thus, an acyloxycyanation strategy can be achieved in good yields and high regioselectivity of either 6-endo or 5-exo cyclization products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 69 publications
0
20
0
Order By: Relevance
“…But, when Cu(OAc) 2 /N‐iodosuccinamide (NIS)/(Me 3 Si) 2 corresponding 5‐exo acyloxy cyanation product was obtained in good yields (See Figure 39). [50] …”
Section: Organic Cyanide Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…But, when Cu(OAc) 2 /N‐iodosuccinamide (NIS)/(Me 3 Si) 2 corresponding 5‐exo acyloxy cyanation product was obtained in good yields (See Figure 39). [50] …”
Section: Organic Cyanide Sourcementioning
confidence: 99%
“…But, when Cu(OAc) 2 /N-iodosuc- cinamide (NIS)/(Me 3 Si) 2 corresponding 5-exo acyloxy cyanation product was obtained in good yields (See Figure 39). [50] Copper acetate assisted the aryl CÀ H bond cyanation by using AIBN molecules supplying "CN" radicals. The aforemen-tioned technique provided an innovative and facile technique for producing aryl nitriles using appropriate amounts of the copper based catalyst.…”
Section: Acetonitrilementioning
confidence: 99%
“…To further investigate the reaction, we changed R 2 from phenyl to alkyl ( t ‐Bu), despite of the huge steric hindrance, the reaction conducted well to afford the 2 w with 80% yield. If a Me 3 Si group was connected to the alkyne ( 1 x ), the reaction tended to afford product 2 xa in 42% yield with another unidentified byproduct 2 xb [18] . When Me 3 Si was replaced by Et 3 Si, 2 y was obtained with yield 45%, and there was no byproduct detected.…”
Section: Resultsmentioning
confidence: 99%
“…Intramolecular cyclization of alkynylbenzoates or o ‐alkynyl benzoic acid is one of the most efficient and straightforward methods to construct the functionalized isocourmarins. As far, a variety of functional groups including Cl, [15] Br, [16] I, [17] CN, [18] SPh, [19] SePh, [20] TePh [21] and SCF 3 [22] have been successfully introduced into isocourmarins. It is worth mentioning that most of these reactions involve the participation of electrophiles or experience cationic intermediates, and the formation of onium ions has been speculated the key step to proceed with the functionalization of alkynes.…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, Shen et al reported a regioselective sequence iodolactonization/acyloxycyanation starting from potassium 2alkynylbenzoate catalyzed by copper(II) acetate in presence of silver acetate (Scheme 7). [12] The authors demonstrated herein that the choice of the carboxylate nucleophile and the iodinated agent allowed to control the regioselectivity, as the 6endo-dig compounds were obtained in different conditions. The corresponding cyanated phthalides were thus obtained with average to good yields as single diasteroisomers and with a good substrate scope.…”
Section: Cu-mediated Reactionsmentioning
confidence: 99%